A Case of Diffuse Leptomeningeal Glioneuronal Tumor Misdiagnosed as Chronic Tuberculous Meningitis without Brain Biopsy. (2nd July 2018) - Lee, Jung koo; Ko, Hak-cheol; Choi, Jin-gyu; Lee, Youn Soo; Son, Byung-chul
Abstract : Here we report a rare case of diffuse leptomeningeal glioneuronal tumor (DLGNT) in a 62-year-old male patient misdiagnosed as having tuberculous meningitis. Due to its rarity and radiologic findings of leptomeningeal enhancement in the basal cisterns on magnetic resonance imaging (MRI) similar to tuberculous meningitis, DLGNT in this patient was initially diagnosed as communicating hydrocephalus from tuberculous meningitis despite absence of laboratory findings of tuberculosis. The patient's symptoms and signs promptly improved after a ventriculoperitoneal shunting surgery followed by empirical treatment against tuberculosis. Five years later, mental confusion and ataxic gait developed in this patient again despite well-functioning ventriculoperitoneal shunt. Aggravation of leptomeningeal enhancement in the basal cisterns was noted in MRI. An additional course of antituberculosis medication with steroid was started without biopsy of the brain. Laboratory examinations for tuberculosis were negative again. After four months of improvement, his mental confusion, memory impairment, dysphasia, and ataxia gradually worsened. A repeated MRI of the brain showed further aggravation of leptomeningeal enhancement in the basal cisterns. Biopsy of the brain surface and leptomeninges revealed a very rare occurrence of DLGNT. His delayed diagnosis of DLGNT might be due to prevalence of tuberculosis in our country, similarity in MRI finding of prominent leptomeningeal enhancement in the basal cisterns, and extreme rarity of DLGNT in the elderly. DLGLT should be considered in differential diagnosis of medical conditions presenting as communicating hydrocephalus with prominent leptomeningeal enhancement. A timely histologic diagnosis through a leptomeningeal biopsy of the brain and spinal cord in case of unusual leptomeningeal enhancement with uncertain laboratory findings is essential because cytologic examination of the cerebrospinal fluid in DLGNT is known to be negative.